Did the COVID-19 pandemic change internal rural migration patterns in Serbia? - Lukić, Vesna; Lović Obradović, Suzana; Stojilković Gnjatović, Jelena (ERDKUNDE, 2023)
Recent empirical research on internal migration has focused on the change in migration volume, before and after the outbreak of the COVID-19 pandemic, by the degree of urbanization. Less is known about the types of rural areas that are attracting internal migrants. This study aims to explore the changes in internal rural migration patterns in Serbia due to the COVID-19 pandemic, focusing on the types of rural settlements as places of destinations and types of urban settlements as places of the origin of migrants. Relying on the additionally processed official national annual statistical data for the period 2018–2021, we offer findings on the differences in volume and socio-demographic characteristics of migrants across six internal migration flows (from small towns, medium-sized towns, and large cities, to suburban and non-suburban rural settlements). The results reveal that the pandemic affected an increase of rural–rural migration as well as rural in-migration from medium-sized towns. We also find that after an initial drop in values for in- and out-migration rates in 2020, relocation intensity exceeded the pre-pandemic level in 2021, with a positive net migration rate for all age groups except 15–30. The unfavorable economic characteristics of rural in-migrants shifted slightly in pandemic years since the share of active and population with personal means rose in non-suburban settlements, while the percentage of dependent population decreased. The opposite holds for suburban settlements.